The ‘Untreatable’ Fear: A Mixed-Methods Study on the Psychosocial Burden and Catastrophic Cognition in Patients Diagnosed with Multi-Drug Resistant (MDR) Neisseria gonorrhoeae - Felicia Sari; Muhammad Yusuf; Mahmood Abbas; Nadia Khoirina; Wisnu Wardhana Putra; Abdullah Assagaf (Scientia Psychiatrica, 2025)
Introduction: The global emergence of multi-drug resistant (MDR) Neisseria gonorrhoeae threatens a return to the pre-antibiotic era. While the microbiological resistance mechanisms are well-documented, the psychopathological sequelae of being diagnosed with a potentially incurable sexually transmitted infection remain underexplored. This study aims to assess the psychosocial burden and catastrophic cognition in patients with MDR N. gonorrhoeae compared to those with drug-susceptible strains. Methods: We employed a sequential explanatory mixed-methods design. A sample of 200 patients (100 MDR vs. 100 Susceptible) was recruited based on an a priori power analysis to ensure sufficient sensitivity for detecting medium effect sizes. Participants completed the adapted Pain Catastrophizing Scale (PCS), Generalized Anxiety Disorder-7 (GAD-7), and Patient Health Questionnaire-9 (PHQ-9). Subsequently, 20 MDR-positive participants underwent in-depth semi-structured interviews analyzed via Interpretative Phenomenological Analysis (IPA). Results: The MDR group exhibited significantly higher mean scores for catastrophic thinking (PCS: 38.4 versus 14.2, p<0.001), anxiety (GAD-7: 16.5 versus 8.1, p<0.001), and depression (PHQ-9: 14.8 versus 6.5, p<0.001). The adapted PCS showed high internal consistency (Cronbach’s a= 0.94). Qualitative analysis revealed core themes of stigma ("The Leper of the Modern Age") and systemic fear ("The Ticking Time Bomb"). Conclusion: A diagnosis of MDR N. gonorrhoeae precipitates a unique and severe psychological syndrome characterized by high catastrophizing and psychosocial distress. Integrated psychiatric care and cognitive behavioral interventions are essential components of the clinical management for this demographic.